Initial Coin Offerings: Financing Growth with Cryptocurrency Token Sales. (11th November 2019) - Howell, Sabrina T; Niessner, Marina; Yermack, David
Abstract: Initial coin offerings (ICOs) have emerged as a new mechanism for entrepreneurial finance, with parallels to initial public offerings, venture capital, and presale crowdfunding. In a sample of more than 1, 500 ICOs that collectively raise ${\$}$ 12.9 billion, we examine which issuer and ICO characteristics predict successful real outcomes (increasing issuer employment and avoiding enterprise failure). Success is associated with disclosure, credible commitment to the project, and quality signals. An instrumental variables analysis finds that ICO token exchange listing causes higher future employment, indicating that access to token liquidity has important real consequences for the enterprise. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.